SYNTHESIS ALGORITHM OF GEOMETRICAL STRUCTURE OF MIMO RADAR ANTENNA ARRAY - S. A. Gorshkov; P. I. Orgish (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
In the given work the algorithm of calculation of co-ordinates of elements of MIMO radar antenna is presented. Initial data for algorithm are the number of transmitting, receiving elements, and also demanded number of channels of receiving.